Pengaruh Home Care Asuhan Keperawatan Gigi dan Mulut terhadap Skor Gingivitis pada Pasien Diabetes Militus - danan, danan; habibah, siti sabatul; Nuryati, Sri; Rahman, Waljuni Astu (Jurnal Skala Kesehatan, 2026)
Diabetes Mellitus (DM) is one of the leading chronic diseases causing high mortality in Indonesia. Based on the 2018 Riskesdas report, the prevalence of DM reached 8.5%. Patients with DM are more susceptible to oral health problems, including gingivitis. This study aimed to determine the effect of home care dental and oral nursing care on reducing gingivitis scores among DM patients in the Sungai Tabuk Community Health Center Work Area, Banjar Regency. The study used a quasi-experimental design with a pretest-posttest approach. Samples were selected through incidental sampling for one month with a total of 30 respondents. The findings showed a significant reduction in gingivitis scores after the intervention, with an average decrease of 0.8280. Statistical analysis revealed a significance value (Sig 2-tailed) of 0.000, which is lower than α (0.05). Thus, Ho was rejected and Ha was accepted, indicating that home care dental and oral nursing care had a positive effect in reducing gingivitis scores among DM patients. In conclusion, home care interventions are effective in improving gingival health for individuals with DM. It is recommended that Sungai Tabuk Community Health Center integrate home care dental and oral nursing care delivered by dental therapists as part of its community dental health program